Milestones of Moderation in the Messenger’s Dealings -With the People of Medina - An Objective Study- (Islamic Sciences Journal, 2023)
The civil society was a multi-cultural society in norms, religions and cultures, and the nature of a society in this case required wisdom and good management, especially since the Prophet, after the emigration, wanted to build a state based on justice and equality, and achieve harmony and coexistence among the components of this society. There is no doubt that the Prophet succeeded in gathering the different people, under one state, and be good in his dealings with everyone, without exception. Therefore, we need to search for the foundations and milestones that the Prophets followed in his dealings with the people of Medina, for the purpose of benefiting and taking lessons. For this reason, we have devoted this paper to a conversation about moderation and its features in the Prophet - may Allah bless him and grant him peace - dealings with the people of Medina, whether they are Muslims, Jews or hypocrites. That is to find out the most important aspects of moderation in his dealings with the people of the city, and to take lessons from it.
Keywords: Landmarks, Moderation, Dealing, the Prophet, the people of Medina.